The Protective Role of Interleukin-33 in Myocardial Ischemia and Reperfusion Is Associated with Decreased HMGB1 Expression and Up-Regulation of the P38 MAPK Signaling Pathway. - Ma Ruisong (PLoS ONE, 2015)
Interleukin-33 (IL-33) plays a protective role in myocardial ischemia and reperfusion (I/R) injury, but the underlying mechanism was not fully elucidated. The present study was designed to investigate whether IL-33 protects against myocardial I/R injury by regulating both P38 mitogen-activated-protein kinase (P38 MAPK), which is involved in one of the downstream signaling pathways of IL-33, and high mobility group box protein 1 (HMGB1), a late pro-inflammatory cytokine. Myocardial I/R injury increased the level of IL-33 and its induced receptor (sST) in myocardial tissue. Compared with the I/R group, the IL-33 group had significantly lower cardiac injury (lower serum creatine kinase (CK), lactate dehydrogenase (LDH), and cTnI levels and myocardial infarct size), a suppressed inflammatory response in myocardial tissue (lower expression of HMGB1, IL-6, TNF-α and INF-γ) and less myocardial apoptosis (much higher Bcl-2/Bax ratio and lower cleaved caspase-3 expression). Moreover, IL-33 activated the P38 MAPK signaling pathway (up-regulating P-P38 expression) in myocardial tissue, and SB230580 partially attenuated the anti-inflammatory and anti-apoptosis effects of IL-33. These findings indicated that IL-33 protects against myocardial I/R injury by inhibiting inflammatory responses and myocardial apoptosis, which may be associated with the HMGB1 and P38 MAPK signaling pathways.